Fermi-level-managed multi-barrier heterojunction diodes for terahertz detection - Iñigo Belio-Apaolaza; James Seddon; Cyril C. Renaud (Scientific Reports)
Abstract Terahertz heterodyne receivers are essential for enabling coherent, high-sensitivity signal detection. At room temperature, GaAs Schottky barrier diodes remain the leading technology but present limitations, particularly in terms of high local oscillator power requirements and contact reproducibility. The fermi-level-managed barrier diode (FMBD), an all-semiconductor InGaAs/InP heterobarrier diode originally conceived for direct THz detection, has the potential to overcome these challenges. However, the intrinsic performance of the FMBD as a frequency mixer has not been fully reported, and there has been little analysis of how to optimise its epitaxial structure for heterodyne detection. In this study, we implement a semiconductor model to predict the nonlinear IV and CV characteristics of the FMBD based on its epitaxial layers, and conduct harmonic balance simulations to extract its intrinsic conversion loss and noise temperature. The results provide a guide for designing FMBD-based THz mixers, depending on the operating frequency, available LO power, and other design factors. In addition, we introduce a novel device concept: the fermi-level-managed multi-barrier diode (FMMBD), which consists of multiple concatenated heterobarriers. This design mitigates the trade-off between device area and junction capacitance. Simulations indicate the FMMBD improves device sensitivity, with intrinsic simulated noise temperatures approaching 10 $$×$$ the quantum limit.